Effectiveness of a home care teaching program for prostatectomized patients: a randomized controlled clinical trial - Mata, Luciana Regina Ferreira da; Azevedo, Cissa; Bernardes, Mariana Ferreira Vaz Gontijo; Chianca, Tânia Couto Machado; Pereira, Maria da Graça; Carvalho, Emilia Campos de (Revista da Escola de Enfermagem da USP, 2019)
Objective: To evaluate the effectiveness of a teaching program for hospital discharge of patients submitted to radical prostatectomy based on the self-efficacy construct of the Cognitive Social Theory. Method: A controlled clinical trial carried out on a 2-month follow-up of 68 prostatectomized men randomized into intervention group (n = 34) and control (n = 34). The intervention group received routine guidance from the service plus the teaching program. The control group only received routine guidance from the service. The data collection instruments were: sociodemographic and clinical questionnaire, self-efficacy scale, hospital depression and anxiety scale, household care knowledge questionnaire, and an item on satisfaction with a score of 1 to 5. Results: There was a significant difference between the intragroups for satisfaction (p<0.001) and knowledge (p<0.001) of the pre-test to the post-test. In the intervention group, there were significant changes between the times for anxiety (p=0.011) and knowledge (p<0.001). Conclusion: The teaching program with a combination of oral guidance, written instruction and telephone follow-up was effective in improving knowledge about home care and personal satisfaction. Brazilian Registry of Clinical Trials: RBR-5n95rm.